Analisis Kesiapan Klinik Pratama Akbid Muhammadiyah Cirebon dalam Menghadapi Pembayaran Kapitasi Berbasis Kinerja - Ari Nurfikri (Center for Health Policy and Management, 2021)
Performance-based capitation payments complement capitation payments based on the fulfillment of service commitments, which in principle will make adjustments to the capitation received if it does not meet the predetermined indicators. The Primary Clinic Akbid Muhammadiyah Cirebon requires a performance-based analysis of the readiness to face capitation payments. The purpose of this study was to simulate income before and after performance-based capitation adjustments and to see the readiness of the Primary Clinic Akbid Muhammadiyah Cirebon in facing performance-based capitation payments in terms of information, authority, staff, and infrastructure. This research uses an explanatory sequential mixed-method approach. In the first phase, data from primary care in 2020 is simulated so that income is known after adjustment by looking at three indicators. The qualitative phase is carried out by in-depth interviews with clinic leaders, medical support and service coordinators, management coordinators, and medical record staff to analyze the clinic's readiness to face performance-based capitation payments. The results showed that the clinic had not been able to meet all performance-based capitation payment indicators so that the income decreased by Rp. 23,178,200. Preparation from the information side by optimizing the JKN Mobile application as a telemedicine service, in terms of authority with regulations governing non-specialized referrals, from infrastructure side with the repair of computers and internet networks, from the staff side with training in both educational materials and innovative delivery media. The study concluded that the clinic requires system improvements in terms of information, authority, infrastructure, and staff to meet indicators of contact rates, non-specialist outpatient referral ratios, and prolanis participant ratio. Keywords: Contac number, Referral, Prolanis